THE STUDENTS’ PERCEPTIONS OF ENGLISH FOR SPECIFIC PURPOSES (ESP) FOR BUSINESS ADMINISTRATION PROGRAM - Hamid, Irfan; Jawas, Umiati; Mujiono, Mujiono (Cahaya Ilmu Bangsa Institute, 2025)
Perception analysis plays an important role in designing English language courses at higher education levels that apply the English for Specific Purposes (ESP) approach. This study intends to determine the perceptions of Business Administration students at the Open University in learning English, including the perceptions of target learning, and the most dominant. The survey method was applied in this research by distributing questionnaires to 30 students. The results showed that out of 30 students who were the respondents, Most students are motivated to learn English in order to have the ability to communicate orally in English and get a good job after graduation. However, most students have difficulty in understanding grammar. From the results, it can be concluded that speaking and writing skills can be further improved through learning activities to discuss topics or problems related to the field of ESP courses for Business Administration program students in The Open University. Analisis persepsi memegang peranan penting dalam merancang mata kuliah bahasa Inggris di tingkat universitas yang menerapkan pendekatan Bahasa Inggris dengan Tujuan Khusus (ESP). Penelitian ini bertujuan untuk mengetahui persepsi mahasiswa Administrasi Bisnis di Universitas Terbuka dalam mempelajari bahasa Inggris, termasuk persepsi terhadap target pembelajaran, dan yang paling dominan. Metode survei digunakan dalam penelitian ini dengan menyebarkan kuesioner kepada 30 mahasiswa. Hasil penelitian menunjukkan bahwa dari 30 mahasiswa yang menjadi responden. Sebagian besar mahasiswa termotivasi untuk belajar bahasa Inggris agar memiliki kemampuan berkomunikasi secara lisan dalam bahasa Inggris dan mendapatkan pekerjaan yang baik setelah lulus. Namun, sebagian besar siswa mengalami kesulitan dalam memahami tata bahasa. Dari hasil penelitian dapat disimpulkan bahwa keterampilan berbicara dan menulis untuk lebih ditingkatkan melalui kegiatan pembelajaran dengan mendiskusikan topik-topik atau permasalahan yang berkaitan dengan bidang mata kuliah ESP bagi mahasiswa program studi Administrasi Bisnis di Universitas Terbuka.